PENGARUH TERAPI BERJEMUR TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA RESPONDEN TERINDIKASI DIABETES MELITUS - Andini, Ary; Kardina, Rizki Nurmalya; Anita (MEDIA ILMU KESEHATAN, 2020)
Background: Vitamin D deficiency could increase the risk of of cancer, autoimmune reaction, cardiovascular disorders, and diabetes mellitus. Objective: The aims of study is to determining effectivity of sunbathing therapy in the morning on blood glucose levels of respondents whose indicated diabetes mellitus type 2. Methods: The study was an quasy experimental study that used 20 respondents whose indicated diabetes mellitus type 2. Afterwards, respondents divided into two group such as control group with no therapy intervention and treatment group with intervention of sunbathing therapy in the morning. Blood glucose levels of each respondent was tested using point of care testing (POCT) on pre and post therapy. Member of treatment group did sunbathing therapy in the morning for 10 minutes in a week. Results: Based on this research showed that blood glucose levels on treatment group lower than control group. Treatment group obtained blood glucose levels from 316,1 ± 99,3 mg/dl decrease into 210,9 ± 81,9 mg/dl significantly (p <0,05) after therapy carried out. But, on control group obtained blood glucose levels from 299,1 ± 75,2 increase into 373,1 ± 68,1 mg/dl significantly (p <0,05). Conclusion: Sunbathing therapy in the morning for 10 minutes had effect to decrease blood glucose levels